2020
DOI: 10.1177/0885066620939055
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Associated With Decreased Time Spent at Home After Critical Illness: A Population-Based Study

Abstract: Background: Frailty is characterized by vulnerability to stressors due to an accumulation of multiple functional deficits. Frailty is increasingly recognized as a risk factor for accelerated functional decline, increasing dependency, and risk of mortality. The objective of this study was to examine the association of frailty, at the time of critical care admission, with days alive at home and health care costs post-discharge. Methods: This retrospective cohort study used linked administrative data (2010-2016) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…(HCRS), Discharge Abstract Database (DAD), National Ambulatory Care Reporting System, and the Continuing Care Reporting System (CCRS) (e-Appendix 1). As in earlier studies of acute hospital care and older adults receiving home care services, 21,22 including of home care client outcomes after ICU admission, 23 these datasets were linked using unique identifiers.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…(HCRS), Discharge Abstract Database (DAD), National Ambulatory Care Reporting System, and the Continuing Care Reporting System (CCRS) (e-Appendix 1). As in earlier studies of acute hospital care and older adults receiving home care services, 21,22 including of home care client outcomes after ICU admission, 23 these datasets were linked using unique identifiers.…”
Section: Data Sourcesmentioning
confidence: 99%
“…18,19 Frailty Index scores of > 0.2 indicate varying degrees of ascending risk. 23,32 For ease of reporting frequencies and class-level hazard ratio statistics, we categorized individuals into levels using increments of 0.1. Finally, the Changes in Health, End-Stage Disease, Signs, and Symptoms Scale (CHESS), although it was not developed explicitly as a frailty measure, 33 performs well in predicting institutionalization, hospitalization, and mortality in home care populations.…”
Section: Exposures: Frailty Measuresmentioning
confidence: 99%
“…36 A 2017 meta-analysis of 10 prospective cohort studies of moderate quality (mean Newcastle-Ottawa Scale score 6.5) found that pre-hospital frailty was associated with increased hospital mortality (relative risk [RR] 1.71, 95% confidence interval [CI] 1.43-2.05) and long-term mortality (RR 1.53, 95% CI 1.40-1.68), independent of age or illness severity. 27 Several studies have reported an incremental increase in mortality for each additional point on the Clinical Frailty Scale (CFS), 27,33,37,38 particularly in those with severe or very severe frailty (CFS ≥ 7). 31,38 Understanding the impact of frailty on ICU prognosis shifts the concern from a patient's age toward their overall clinical status and trajectory before ICU admission.…”
Section: What Is the Relevance Of Pre-existing Frailty For Critically Ill Older Adults?mentioning
confidence: 99%
“…27 Several studies have reported an incremental increase in mortality for each additional point on the Clinical Frailty Scale (CFS), 27,33,37,38 particularly in those with severe or very severe frailty (CFS ≥ 7). 31,38 Understanding the impact of frailty on ICU prognosis shifts the concern from a patient's age toward their overall clinical status and trajectory before ICU admission.…”
Section: What Is the Relevance Of Pre-existing Frailty For Critically Ill Older Adults?mentioning
confidence: 99%
“…Une méta-analyse de 2017 regroupant 10 études de cohorte prospectives de qualité modérée (score de Newcastle-Ottawa moyen 6,5) a révélé que la fragilité préhospitalière était associée à une hausse de la mortalité hospitalière (risque relatif [RR] 1,71, intervalle de confiance [IC] à 95 % 1,43–2,05) et de la mortalité à long terme (RR 1,53, IC à 95 % 1,40–1,68), indépendamment de l’âge ou de la gravité de la maladie 27 . Plusieurs études ont signalé une augmentation de la mortalité à chaque point additionnel à l’échelle de fragilité clinique (EFC) 27 , 33 , 37 , 38 , particulièrement chez les individus présentant une grande ou une très grande fragilité (EFC ≥ 7) 31 , 38 . Comprendre l’incidence de la fragilité sur le pronostic à l’USI fait que l’on s’intéresse moins à l’âge du patient et plus à son état clinique global et à sa trajectoire avant son admission à l’USI.…”
Section: Pourquoi Tenir Compte De La Fragilité Préexistante Des Personnes âGées Gravement Malades?unclassified